CRISPR/Cas9-mediated inactivation of the soybean agglutinin Le1 gene to improve grain quality - Kafer, João Matheus; Koltun, Alessandra; Hoshino, Rodrigo Thibes; Girotto, Larissa; Silveira, Cesar Augusto; Marin, Silvana Regina Rockenbach; Rech, Elibio Leopoldo; Nepomuceno, Alexandre Lima; Mertz-Henning, Liliane Marcia (Frontiers in Plant Science, 2026)
IntroductionSoybean agglutinin (SBA) is a major antinutritional factor in soybean seeds, reducing digestibility in monogastric animals. The Le1 gene encodes the primary lectin accumulated in seeds. Genome editing offers a direct strategy to eliminate this factor in elite cultivars.MethodsTwo gRNAs targeting Le1 were inserted into a CRISPR/Cas9 binary vector and used for Agrobacterium tumefaciens–mediated transformation of the soybean cultivar BRS 537. Edited plants were screened by PCR, Sanger sequencing, protein electrophoresis (SDS-PAGE), hemagglutination assays, and segregating generations were tested to identify transgene-free progeny. Agronomic traits were evaluated under field conditions.ResultsTwenty transformation events were generated, with an editing efficiency of 10%. Event AF12-13-1 carried a 4-bp deletion producing a truncated, unstable lectin protein. SDS-PAGE confirmed the absence of the ~30 kDa SBA band, and hemagglutination assays showed complete loss of lectin activity. Transgene-free T2 plants lacking Bar, Cas9, and AtU6 sequences were identified. Agronomic traits—including yield and thousand-seed weight—were comparable to the wild-type cultivar.DiscussionCRISPR/Cas9 editing of Le1 effectively eliminated SBA accumulation without compromising key agronomic traits. The resulting low-lectin soybean lines represent a promising approach to improve digestibility and feed efficiency for monogastric animals.